Current trends in production, morphology, and real-world environmental applications of biochar for the promotion of sustainability. (September 2022) - Uday, Vismaya; Harikrishnan, P.S.; Deoli, Kanchan; Zitouni, Faiza; Mahlknecht, Jürgen; Kumar, Manish
Graphical abstract: Highlights: Real-world possible applications of biochar for environmental sustainability are reviewed. Benefits of biochar is linked with ways of attaining sustainable development goals. Preparation methods and source materials determine the carbon content of biochar. Carbon sequestration and contaminant adsorption abilities of biochar needs further exploration. Biochar has enormous potential to contribute toward waste, energy and pollution management. Abstract: Biochar has sparked a lot of interest in recent years for various applications such as contaminant removal, carbon sequestration and soil amendment. However, laboratory scale studies dominates over the real-world applications. In this study, we first enumerated on the various ongoing uses of biochar along with adsorption mechanism; and then identified the most suitable source, and efficient method for biochar production; and finally proposed real-world practical applications of biochar as an additive to control diffuse micropollutant pollution along the highways and railway tracks; as well as the pollution through agricultural runoff. We demonstrated that directly or indirectly, biochar can definitely help to achieve all the 17 Sustainable Development Goals. The study on the practical use of biochar is an emerging area, because a lot of research needs are there to realise the full-potential of biochar with ways of attaining sustainable development goals towards waste, energy and pollution management.